Tobin’s Q as a Mediating Variable in the Relationship between Financial Ratios and Stock Prices: An Analysis - Suseno, Giri; Putri, Endah Arianti; Sari, Nurmala; Meilita, Willi (E-Jurnal Akuntansi; Vol 34 No 5 (2024)DO - 10.24843/EJA.2024.v34.i05.p01, 2024)
Other sectors of the economy depend on Indonesia's financial industry for liquidity and loans. Therefore, studying the components that influence the value of banking stocks is interesting and important. This study investigates the mediating effect of Tobins's Q on the correlation of Price Earnings Ratio, Price to Book Value, and Earning per Share to Share Price in the Indonesian banking sector. This quantitative research uses the partial least squares-structural equation modelling (PLS-SEM) method. This study examined 43 banks listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022 with a total of 172 data for 4 years. Purposive sampling was used by the researchers. Tobin's Q is a positive mediator, although it does not statistically significantly influence EPS and PER on Share Price. In addition, Tobin's Q is also a negative mediator of PBV and Share Price, but not statistically significant. This research has major implications for managerial decision-making, investor tactics, regulatory rules, and future research on stock prices and corporate management. Keywords: Tobin's Q; Price Earnings Ratio; Price to Book Value; Earning per Share; Stock price.